2003
DOI: 10.1590/s0104-12902003000200009
|View full text |Cite
|
Sign up to set email alerts
|

A geração de maus odores na rede coletora de esgotos do município de Pereira Barreto: um problema de saúde pública

Abstract: A presença de sulfetos, principalmente o de hidrogênio, é responsável pela geração de odores e pelo processo de corrosão nas instalações de coleta e tratamento de esgotos. O presente trabalho foi desenvolvido com base em uma pesquisa com a população do município de Pereira Barreto. O resultado desse estudo foi utilizado para identificar e analisar os problemas causados pela geração de maus odores na rede coletora de esgotos local, devido a formação do sulfeto de hidrogênio, focalizando a questão como problema … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…The WWTPs that use the anaerobic treatment produce biogas. However, the untreated biogas emission into the atmosphere creates a problem relating to the stations which are installed near the housing area, as the population has rejected these practices due to the presence of odor, health problems associated to odoriferous substances and estate speculation LILIAMTIS;MANCUSO, 2003;SILVA, 2007). Krischan, Makaruk and Harasek (2012) highlight the importance of studying a H 2 S removal selective technique, further using cheap and environmentally safe reagents.…”
Section: Advantages Disadvantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The WWTPs that use the anaerobic treatment produce biogas. However, the untreated biogas emission into the atmosphere creates a problem relating to the stations which are installed near the housing area, as the population has rejected these practices due to the presence of odor, health problems associated to odoriferous substances and estate speculation LILIAMTIS;MANCUSO, 2003;SILVA, 2007). Krischan, Makaruk and Harasek (2012) highlight the importance of studying a H 2 S removal selective technique, further using cheap and environmentally safe reagents.…”
Section: Advantages Disadvantagesmentioning
confidence: 99%
“…On the other hand, Liliamtis and Mancuso (2003) studied the odor perception of hydrogen sulfide coming from a wastewater treatment plant in the city of Pereira Barreto -São Paulo. The authors reported there was a complaint about odor of "rotten eggs" in addition to health problems, such as headaches, nausea, mood swings and dizziness.…”
Section: Hydrogen Sulfide and Its Main Characteristicsmentioning
confidence: 99%
“…The process of urbanization that began in Brazil in the 1950s has contributed to the degradation of the quality of its urban rivers (Gorski, 2010). One of the main contributing factors associated with this process is the lack of adequate sanitary sewage services (Liliamtis and Mancuso, 2003). In 2015, the United Nations established a blueprint for the purpose of transforming the world, expressed in the form of 17 Sustainable Development Goals (SDG).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, houses that are connected to a sanitary sewer network but improperly discharge their waste into storm drains also contribute to the contamination of water bodies, the generation of foul odors and the persistence of public-health problems (Liliamtis and Mancuso, 2003;Shamsollahi et al, 2019). Thus, the implementation of a sewage collection system alone does not guarantee public health, since households must be correctly connected to the network in order to derive any benefit from these public works.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac and respiratory symptoms (e.g. tachycardia, palpitations and cardiac arrhythmias, bronchitis, pulmonary edema, respiratory depression and respiratory paralysis, usually accompanied by nausea, vomiting and diarrhea) are related to acute exposure, whereas chronic exposure can lead to neurological problems, which include dizziness, irritability, headache, seizures and even coma (LILIAMTIS and MANCUSO, 2003).…”
Section: Introductionmentioning
confidence: 99%